THE BACKGROUND AND THE UNDERLYING CAUSES OF DINUZULU'S SECOND BANISHMENT FROM ZULULAND (Historia, 2021)
After Cetshwayo's deposition at the end of the Anglo-Zulu War of 1879 he was allowed to re.turn to Zulu land in 1883. He was, however, to have auti}ority only over a part of Zululand. The other part was given to his British-supported enemy, Zibhebhu. Conse-quently, the ground for unrest was laid because war soon broke out between the Usuthu and the Mandlakazi. The Civil War continued until February 1884, when Cet-shwayo died in a kraal near Eshowe. In an attempt to avenge his father's death and to regain the Usuthu lands taken by the Mandlakazi, Dinuzulu solicited Afrikaner aid. In May 1884, a party of Afrikaners from the Transvaal under Coenraad Meyer recognis-ed Dinuzulu as th~new king. Consequently, the Usuthu, supported by the Afrikaners, decisively crushed Zibhebu's forces at the Battle of Tshaneni on 5 June 1884. Unfortunately the British authorities were against the revival of the Zulu kingdom, hence the annexation of Zululand in May 1887 and the resettlement of Zibhebhu in the Ndwandwe district giving him virtual free reins to molest Dinuzulu. This was the background to the Usuthu revolt of 1888 which, after an unjust trial, led to the banishment of Dinuzulu and his uncles Ndabuko and Shinganato St. Helena.1 Dinuzulu's second banishment in 1909 can be understood by looking at the con- editions of his return from St Helena, his reconciliation with Zibhebhu in 1898 and the subsequent reaction from the Minister for Native Affairs in Natal, the succession to the Mandlakazi tribe, and the warning by James Crosby about the Zulu dissatisfaction in 1905.
Keywords: Zibhebhu; Crosby, J.,; History; Zulu dissatisfaction; Reconciliation acts; Dinuzulu; Mandlakazi tribe; Anglo-Zulu wars